CONCEPTUALIZATION OF POLITICAL INNOVATIONS IN CONTEMPORARE UKRAINIAN POLITICAL PROCESS - Фоломєєв, М.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The use of sociological and economic conceptions of innovation in the plane of political science is grounded. Attention is accented on judicial nature of innovation in a policy, its determination, including as internal effective mechanism of development of the system. The agents of innovation, procedure of its realization and stages of innovative process from the system and subjective point of view, and also possible reactions on introduction of innovation are described.